Can a Christian peasant offer a "payment to the land"? - Marzal, Manuel (1971)
I have just been in the parish of Taraco (province of Huancané, Puno), one of the two Quechua parishes that the Aymara prelature of Juli has. I have been collecting material for a study on the peasant priesthood. I have spoken with Fr. Tomás Verhoeven, M.M., promoter of the rural catechetical movement in the mountains and founder of the schools in Puno, Cusco, Huancayo and Huaraz. Now Father Tomás is directing his catechesis to the formation of grassroots Christians. One day, after the meeting with the grassroots Christians of the Patascachi bias, one of them asked me: can a Christian offer a payment to the land? This question is the starting point of these pages, which try to guide the resolution of this "case of conscience" for the majority of the peasants of the so-called "Indian spot" (Huancavelica, Ayacucho, Abancay, Cuzco and Puno), that during the nights of the month of August they gather in their houses to offer the payment to the pachamama.